Analysis of the use of exercise imagery functions by exercisers in Nigeria (2011)
It is a general position that imagery plays a cognitive behavioral role in enhancing the performance of sport skills as noted in Short and Short (2005), the use of imagery is also more equally significant in exercise activities and can bring to fruition the performance of an individual exerciser because of its unique motivational function. Research studies has been conducted, examining imagery use by different categories of participants related to sport and exercise in the developed world, there have been dearth of literature on imagery use on similar participants in the deve1oping countries, hence the purpose of this study. Participants (482) male and female students were recruited from universities of Nigeria (mean age 24.0 ±SD4,7; male, n=256) and (mean age 23.0±SD5.2, female, n=226). A demographic questionnaire and the Exercise Imagery Questionnaire (EIQ) Hausenblas et. a1 (1999) were used for data collection. Results indicated that no significant difference (p>0.5) was found on the three imagery functions by sex. But significant difference (p<0.5) was located on the appearance imagery function based on the criterion independent variables of three exercise activity groups of the exercise participants.